Linguo poetic analysis of Osman Azim's poems: (Based on the poem "Comments on the pronouns in the garden") - qizi, Uralova Aziza Dilmurod; Abdujabborovna, Buranova Rano (European Journal of Life Safety and Stability (2660-9630), 2021)
In Osman Azim's poem "Comments on the words in the garden", the words of encouragement appear as an important tool in expressing the feelings of the lyrical hero. In this poem, the feelings of the human soul are described in harmony with the image of natural phenomena, the change of seasons, in addition to words.